Mechanism of scaphoid waist fracture: finite element analysis. (May 2023) - Santoshi, John Ashutosh; Behera, Prateek; Dwivedi, Ravi Kumar; Srivastav, Ayush
The mechanism of scaphoid waist fracture is not completely understood. We used finite element analysis to study the formation of scaphoid waist fractures. Clinical computed tomography scans of 12 wrists were used to create models for finite element analysis. The points of application of load were at different sites along the scaphotrapeziotrapezoid joint distally, and the scaphoid fossa plus the area underlying the radioscaphocapitate ligament was regarded as the fixed proximal support. A fracture was produced at the scaphoid waist in all cases. The location of failure of bone at its anterior or dorsal cortex, either in tension or in compression, was determined by the site of application of the load. The anterior cortex failed in compression when the point of impact was located along the trapezium facet or the entire distal pole, whereas it failed in tension when the point of impact was along the trapezoid facet.